Normative Data for Test of Verbal Fluency and Naming on Ecuadorian Adult Population - Rodríguez-Lorenzana, Alberto; Benito-Sánchez, Itziar; Adana-Díaz, Lila; Paz, Clara Patricia; Yacelga Ponce, Tarquino; Rivera, Diego; Arango-Lasprilla, Juan Carlos (Frontiers in Psychology, 2020)
Objective: To generate normative data for verbal fluency and naming test in an Ecuadorian adult population. Methods: The sample consisted of 322 healthy adults (18–84 years old) recruited from Quito, Ecuador. The verbal fluency and Boston Naming Test (BNT) were administered as part of a larger comprehensive neuropsychological battery. Multiple linear regression analyses were used to generate the normative data taking into account age, education, and sex. Results: For phonological verbal fluency, results indicated that only education was significantly related to the performance of the letters “A,” “S,” and “M.” However, the performance on the letter “F” was significantly associated with age and education. For semantic fluency, the performance on “animals” was significantly influenced by age, quadratic age, and education, whereas that for “fruits” was explained by quadratic age, education, and sex. The performance on the BNT was significantly influenced by age and education. A Microsoft Excel-based calculator was created to help clinicians to obtain the normative data on this test. Conclusion: This normative data will help neuropsychologist in Ecuador to use these tests both in research and in their clinical practice to improve the diagnosis of cognitive deficits in the population.